Evaluating information on coronavirus in the Central-West region of Brazil using the database of the brazilian information system - Santos, Wilker José Caminha dos; Santos, Marcus Rhuan Caminha dos; Carr , Renato Ferreira (Seven Editora, 2023)
The present work addresses the importance of data analysis to understand the COVID-19 pandemic and its impact in the Midwest region of Brazil. The need for an accurate and correct analysis is highlighted to ensure the adequate allocation of resources in the fight against the disease. The text also describes the steps involved in conducting research on the coronavirus, including proposal, literature review, data quantification, and statistical analysis. According to the Ministry of Health, COVID-19 is caused by the SARS-CoV-2 coronavirus and can range from asymptomatic infections to severe controlled conditions. Most patients (about 80%) may be asymptomatic, while about 20% of cases may require hospital care and approximately 5% may require ventilatory support. The disease is caused by a virus that lives in the controlled tract of bats and may have undergone a mutation process to install itself in the human body. The main symptoms are fever, shortness of breath, dry or secret cough, and sore throat. So far, there is no specific vaccine for the new coronavirus, but at least eight types of vaccines are being made in humans in search of the most efficient immunization. Keywords: Coronavirus, database, perception, solution. Results are presented using line graphs and tables, providing a clear picture of the current situation and informing the public on how to identify and seek treatment for the disease. DOI:https://doi.org/10.56238/emerrelcovid19-022